Leishmania donovani p36(LACK) DNA Vaccine Is Highly Immunogenic but Not Protective against Experimental Visceral Leishmaniasis - Melby, Peter C. (American Society for Microbiology, 2001)
The acquisition of immunity following subclinical or resolved infection with the intracellular parasite Leishmania donovani suggests that vaccination could prevent visceral leishmaniasis (VL). The LACK (Leishmania homolog of receptors for activated C kinase) antigen is of interest as a vaccine candidate for the leishmaniases because of its immunopathogenic role in murine L. major infection. Immunization of mice with a truncated (24-kDa) version of the 36-kDa LACK antigen, delivered in either protein or DNA form, was found previously to protect against cutaneous L. major infection by redirecting the early T-cell response away from a pathogenic interleukin-4 (IL-4) response and toward a protective Th1 response. The amino acid sequence of the Leishmania p36(LACK) antigen is highly conserved, but the efficacy of this vaccine antigen in preventing disease caused by strains other than L. major has not been determined. We investigated the efficacy of a p36(LACK) DNA vaccine against VL because of the serious nature of this form of leishmaniasis and because it was unclear whether the LACK vaccine would be effective in a model where there was not a dominant pathogenic IL-4 response. We demonstrate here that although the LACK DNA vaccine induced a robust parasite-specific Th1 immune response (IFN-γ but not IL-4 production) and primed for an in vivo T-cell response to inoculated parasites, it did not induce protection against cutaneous or systemic L. donovani challenge. Coadministration of IL-12 DNA with the vaccine did not enhance the strong vaccine-induced Th1 response or augment a protective effect.